A rare case of premenarchal ovarian abscess presenting as an acute abdomen - B Jagdish; Enono Yhoshu; Balija Satya Sree; Gaurav Sharma; Himanshu Menghwani (Wolters Kluwer Medknow Publications, 2023)
Ovarian abscesses are usually seen in females of reproductive age group. They may occur secondary to urinary tract infections, pelvic inflammatory diseases, or gastrointestinal infections. They are uncommon in premenarchal females. They can be either managed conservatively with antibiotics and analgesics or may require surgery. In this case report, we present the case of a 6-year-old female who presented to us with an acute abdomen, which was diagnosed as a case of ovarian abscess and improved on exploration and drainage.